EFFECT OF SERVICE FEATURES AND WORD OF MOUTH STRATEGY ON CUSTOMER DECISIONS IN USING BSI MOBILE - Indah Aulia Indayani (Journal of Economic Development and Village Building, 2024)
This study aims to determine the effect of Service Features and word of mouth strategies on customer decisions in using BSI Mobile banking. Research using quantitative methods. The location of this research took place at Bank Syariah Indonesia Cirebon KCP Plered 2. The population in this study was 4005. Calculated based on the Slovin formula, a sample of 100 participants was obtained. The instrument used is a questionnaire or a questionnaire. instrument validity used product moment validity and reliability used Croncbach's alpha. Data collection techniques through the distribution of questionnaires, interviews, and observation. Data analysis used included research instrument tests, classical assumption tests, multiple linear regression tests, and hypothesis. The results showed that part there was a significant positive effect of service features on customer decisions in using Mobile Banking for BSI Cirebon customers. KCP Plered 2 with a significant value of 0.000. Meanwhile, according to word of mouth, most of the variables did not have a significant positive effect on the customer's decision to use mobile banking for BSI Cirebon KCP Plered 2 customers with a significant value of 0.696. Simultaneously the influence of service feature variables and word of mouth contributed 22.75% to customer decisions in using BSI Mobile banking.